The Stability and Antioxidant Activity of Anthocyanins from Blueberry - Rui He; Zhi Min Li; Bo Chu Wang (Food Technology and Biotechnology, 2010)
Anthocyanins from highbush blueberry (Vaccinium corymbosum L.) have tremendous potential as natural colorants and functional food with pharmaceutical purposes in food applications. To exploit the potential for food applications, the stability and antioxidant activity of anthocyanins present in blueberries have been studied. The results indicate that anthocyanins from blueberry were stable against the low pH (≤5.0), NaCl (0.125–0.500 mol/L), sucrose (0.584–2.336 mol/L) and preservative (sodium benzoate, 0.035–0.140 mol/L), but were sensitive to alkaline conditions (≥7.0), high temperature (≥80 °C), light (natural light), oxidizing agent (H2O2, 0.5–2.0 %) and reducing agent (Na2SO3, 0.005–0.040 mol/L). At concentrations of 25 and 50 mg/mL, anthocyanins from blueberry could protect ECV-304 cells against oxidative damage induced by H2O2. These results suggest that anthocyanins from blueberry can be regarded as a potential colorant for some acidic (pH≤5.0) food products and could be used as health food to prevent diseases arising from oxidative processes.